(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The goal of the search is to Diagnosing the level of awareness and response of the researched sample to the concept of enlightened leadership and strategic alignment, as well as measuring the strength and weakness of the correlations and influence between the independent variable enlightened leadership with its dimensions represented by (the role of the developer, the role of the changer, the role of the visionary, the role of the communicator) and the dependent variable strategic alignment with its dimensions represented by ( Cultural alignment, structural alignment, technological alignment, resource alignment). Accordingly, the research problem was defined by the main question to identify the role that enlightened leadership plays in achieving strategic alignment in a number of private Iraqi commercial banks, represented by (Iraqi Middle East Investment, Business Gulf, and Ashur International). ، Al-Mansour Investment, Baghdad, Iraqi Investment)، and in light of this, the hypothetical plan for the research was designed, which embodies the relationship between the research variables. The descriptive analytical approach was adopted and the questionnaire was used as the main tool for collecting data from the sample of (124) respondents representing administrative leaders at various levels. ( Delegate Director, Assistant Delegate Director, General Manager, Assistant General Manager, Department Director, Assistant Department Director, Division Official ), as well as the use of data and reports. Financial statements for the years (2017-2021) for the investigated banks. Statistical methods were used to analyze the data (arithmetic mean, standard deviation, coefficient of variation, relative importance , Pearson correlation coefficient, Spearman correlation coefficient, regression coefficient, t-test , coefficient of determination R² , F -test Confirmatory factor analysis , Kruskal-Wallis test ) and based on the two statistical programs )SPSS v.28 ) and ( AMOS v.26 , and the research concluded a set of results,( the most important of which is the existence of a correlation and impact of leadership enlightened by its dimensions in achieving strategic alignment, which indicates the importance of the role of leadership enlightened by its dimensions in achieving strategic alignment and then achieving decent work and the economic growth